Green Marketing Strategy And Intention To Visit Eco-Friendly Tourist Attraction - Kukuh Mulyanto; Akhmad Nurofi; Asepta Hendriyanto; Waode Sitti Nurrohma (International Conference On Digital Advanced Tourism Management And Technology, 2023)
This study aims to examine the effect of green marketing components, namely green products, and green promotions on visit intentions. The population and sample of this research are visitors to the Tugurejo mangrove forest conservation tourism object. The sampling technique used was purposive sampling. Primary data was used in this study, with data collection techniques through online questionnaires. The results showed that green product and green promotion had an effect on intention to visit.